Pengaruh Kedisiplinan Belajar dan Lingkungan Sosial terhadap Hafalan Al-Qur'an Santri Pesantren Imam Syafi'i Dramaga Bogor - Didin Juandi; Edy; Hasan Bisri (STIT Sirojul Falah Bogor, 2026)
This study analyzes the influence of learning discipline and social environment on students' (santri) Qur'an memorization (tahfizh) achievement at Pondok Pesantren Imam Syafi'i Dramaga, Bogor. It was motivated by the fact that despite strict discipline and a structured religious environment, santri's memorization achievement still varies considerably. Using a quantitative, correlational-predictive design with multiple regression, data were collected from 235 santri selected through proportional random sampling (Slovin formula) from a population of 291, via three validated Likert-scale questionnaires (Cronbach's Alpha: 0.831, 0.742, 0.771). Analysis using IBM SPSS Statistics 26 revealed that learning discipline (t = 10.936; Sig. = 0.000) and social environment (t = 2.953; Sig. = 0.003) each have a positive, significant partial effect on memorization achievement. Simultaneously, both variables significantly influence memorization achievement (F = 102.411; Sig. = 0.000), contributing 46.9% (R² = 0.469). These findings support Kurt Lewin's Field Theory and imply that pesantren should strengthen discipline while fostering a supportive social environment. Keywords: learning discipline; multiple regression; pesantren; Qur'an memorization; social environment